If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + v = 15 Solving 12 + v = 15 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + v = 15 + -12 Combine like terms: 12 + -12 = 0 0 + v = 15 + -12 v = 15 + -12 Combine like terms: 15 + -12 = 3 v = 3 Simplifying v = 3
| x=-3/4y+2/3 | | 2+cos^2x=3sin^2x | | x-2+5=-9 | | 3s=-13 | | 2*3/4 | | -5(y+3)=-7y-1 | | y=-2*1+3 | | (3x^2-2x)/(5x-1)=0 | | 3w+5/2w+8 | | 2*5*1.5-1-3=11 | | 2(x-2)=5(x+5) | | 2/5*7 | | 7f-2=9 | | 3Q^2-42Q+160=0 | | 2(5x+10)=-5x-40 | | 10-(4-2x)=4 | | 17-n=79 | | 2*5*1.5-1-3= | | 18y+9-28*9y+9=0 | | ln(x+3)+ln(x-3)=5t | | 2*5x-1-3=11 | | 7.3*X=6.8 | | 3(2x-6)=-2(x+2) | | 28=0.001(0.732x^2+15.417x+605.738) | | (-5x^2)+9x+8=0 | | 3*(3/4)^2-(2*3/4) | | -5u-(7/2)=(1/3)u-(4/3) | | -6v-11=5v | | 8(v+1)-4v=2(2v+4)-16 | | -.8t+.4=.66666666667 | | (7+3)/2+3x8 | | 24-1/28(3x)=16-1/28(2x) |